Item and distracter analysis of multiple choice questions (MCQs) from a preliminary examination of undergraduate medical students - Sahoo, Durgesh Prasad; Singh, Rakesh (International Journal of Research in Medical Sciences, 2017)
Background: Multiple choice questions (MCQs) or Items forms an important part to assess students in different educational streams. It is an objective mode of assessment which requires both the validity and reliability depending on the characteristics of its items i.e. difficulty index, discrimination index and distracter efficiency. To evaluate MCQs or items and build a bank of high-quality test items by assessing with difficulty index, discrimination index and distracter efficiency and also to revise/store or remove errant items based on obtained results. Methods: A preliminary examination of Third MBBS Part-1 was conducted by Department of Community Medicine undertaken for 100 students. Two separate papers with total 30 MCQs or items and 90 distractors each in both papers were analyzed and compared. Descriptive as well as inferential statistics were used to analyze the data. Results: The findings show that most of the items were falling in acceptable range of difficulty level however some items were rejected due to poor discrimination index. Overall paper I was found to be more difficult and more discriminatory, but its distractor efficiency was slightly low as compared to paper II. Conclusions: The analysis helped us in selection of quality MCQs having high discrimination and average difficulty with three functional distractors. This should be incorporated into future evaluations to improve the test score and properly discriminate among the students.